Comparison of norse LT-94 (herring meal) to other protein sources in early-weaned starter pig diets - Richert, B.T.; Smith, J.W. II; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two growth trials were conducted to compare Norse LT-94 to other protein sources in starter pig diets. In trial 1, 270 weanling pigs (initially 13.7 lb and 20 d of age) were used to compare Norse LT-94 (herring meal), select menhaden fish meal, and spraydried blood meal as protein sources in the Phase II diet. Pigs were blocked by weight with six replications of three treatments and 15 pigs per pen. During Phase I (d 0 to 7 postweaning), all pigs were fed the same high nutrient density diet. During Phase II (7 to 28 d postweaning), pigs were fed one of three experimental diets. All Phase II diets contained 10% dried whey and were formulated to 1. 25% lysine and .34% methionine. The positive control diet contained 2.5% spray-dried blood meal. Norse LT-94 (herring meal, 4.06%) and select menhaden fish meal (4.87%) replaced blood meal on an equal lysine basis to form the other experimental diets. No differences occurred in pig performance during Phase II, indicating that Norse LT-94, spray-dried blood meal, and select menhaden fish meal are interchangeable as protein sources when substituted on an equal lysine basis. In trial 2, 230 pigs (initially 18 d of age and 11.0 lb) were used to examine the influence of various combinations of spray-dried porcine plasma and Norse LT-94 on starter pig performance. Pigs were allotted by weight to six replicates of five treatments with six to 10 pigs per pen. Pigs were assigned to one of five dietary treatments with no replacement or 25, 50, 75, or 100% of the spray-dried porcine plasma replaced with Norse LT-94 (herring meal) on an equal lysine basis. Therefore, diets contained 8, 6, 4, 2, or 0% spray-dried porcine plasma and 0, 2.14, 4.29, 6.43, or 8.58% Norse LT-94, respectively. All Phase 1 diets were formulated to contain 20% dried whey, 1.5% lysine, and .44% methionine. These diets were fed from d 0 to 14 postweaning. From d 14 to 28 (Phase II), all pigs were fed a common diet. Replacing spray-dried porcine plasma with Norse LT-94 resulted in a linear decrease in average daily gain (ADG) and average daily feed intake (ADFI) during Phase I and for the overall trial. This response became magnified when greater than 25% of the plasma was replaced with Norse LT-94. Feed efficiency responded in a quadratic manner for the first week of Phase I and for the overall trial, with pigs fed the diet containing 6% spray-dried porcine plasma and 2.14% Norse LT94 having the best feed efficiency. These trials indicate that Norse LT-94 (herring meal) can replace spray-dried blood meal and select menhaden fish meal in Phase II starter pig diets. However, Norse LT-94 (herring meal) cannot be used as a replacement for spray-dried plasma protein in the Phase I diet.
Keywords: Swine; Starter; Fish meal; Plasma protein